Experiment Design Analysis of Corrosion Inhibitor from Papaya Leaf Extract for Contextual Chemistry Learning - Fuadatul Mukoningah; Retno Aliyatul Fikroh; Shofrina Surya Dewi (Universitas Sultan Ageng Tirtayasa, 2022)
The implementation of the 2013 curriculum, which focuses on the phenomenon of daily life, is part of the government's effort to improve the quality of education in Indonesia. Corrosion is one of the most common problems, so learning how to overcome corrosion is essential. The tannin content of papaya leaves has the potential to be a corrosion inhibitor. As a result, this study aims to investigate papaya leaf extract as a corrosion inhibitor and its potential as a contextual learning aid. The qualitative descriptive method was used in this study, with data collected through literature studies, observations, interviews, and experiments. The results showed that papaya leaf extract could be used as a corrosion inhibitor with a 73 percent efficiency in using a 20% inhibitor. Based on literature reviews, observations, and interviews with educators and students in Yogyakarta, papaya leaf experiments as an inhibitor can be a contextual learning alternative to corrosion material in senior high school in terms of finances, pedagogy, and human resources readiness.